KUALITAS PELAYANAN HAJI DAN UMRAH PADA KANTOR KEMENTERIAN AGAMA KABUPATEN HULU SUNGAI TENGAH - Murdiansyah Herman; Normajatun Normajatun; Desy Rahmita (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2018)
The purpose of this research is to know the service quality of Hajj and Umrah on Religious Ministry office of Hulu Sungai Tengah Regency. Research method using qualitative approach with descriptive type. Data collected conducing interviews to three informants. Using the technique of descriptive data analysis to draw conclusion. In generale the results showed, hajj and umrah services quality based on tangible, reliability, responsiveness, assurance and emphaty already meet the expectations of users of the service. There are various factor that support an hinder the ministry of hajj and umrah. Factor endowments include sincere attitude in providing service and facilities in the form of a computer and an internet connection. While the factor that inhibit islack the strengthof the internet connection from the central server and the officer who are less reliable and sometimrs arrive late ini providing the service.